An Analytical Bond Order Potential for Mg−H Systems. Issue 10 (31st January 2019) - Zhou, Xiaowang; Kang, Shinyoung; Heo, Tae Wook; Wood, Brandon C.; Stavila, Vitalie; Allendorf, Mark D.
Abstract: Magnesium‐based materials provide some of the highest capacities for solid‐state hydrogen storage. However, efforts to improve their performance rely on a comprehensive understanding of thermodynamic and kinetic limitations at various stages of (de)hydrogenation. Part of the complexity arises from the fact that unlike interstitial metal hydrides that retain the same crystal structures of the underlying metals, MgH2 and other magnesium‐based hydrides typically undergo dehydrogenation reactions that are coupled to a structural phase transformation. As a first step towards enabling molecular dynamics studies of thermodynamics, kinetics, and (de)hydrogenation mechanisms of Mg‐based solid‐state hydrogen storage materials with changing crystal structures, we have developed an analytical bond order potential for Mg−H systems. We demonstrate that our potential accurately reproduces property trends of a variety of elemental and compound configurations with different coordinations, including small clusters and bulk lattices. More importantly, we show that our potential captures the relevant (de)hydrogenation chemical reactions 2H (gas)→H2 (gas) and 2H (gas)+Mg (hcp)→MgH2 (rutile) within molecular dynamics simulations. This verifies that our potential correctly prescribes the lowest Gibbs free energies to the equilibrium H2 and MgH2 phases as compared to other configurations. It also indicates that our molecular dynamics methods can directly reveal atomic processes of (de)hydrogenation of the Mg−H systems. Abstract : Five versions of Mg−H bond order potentials capturing energy and geometry trends of a variety of Mg, H, and Mg−H structures have been developed. All five potentials predict crystalline growth of the rutile MgH2 phase during molecular dynamics simulations. Hence, they can be used to study (de)hydrogenation of magnesium under reactive conditions.